2020
DOI: 10.2463/mrms.ici.2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

4D Flow MR Imaging Reveals a Decrease of Left Atrial Blood Flow in a Patient with Cardioembolic Cerebral Infarction after Pulmonary Left Upper Lobectomy

Abstract: We present the case of a 76-year-old woman who underwent left upper lobectomy for lung adenocarcinoma. Three days after the surgery, a thrombus was observed in the pulmonary vein (PV) stump. Four months after the surgery, we performed 4D flow MRI, which revealed decreased blood flow, not only in the left superior PV stump, but also over a widespread region around the left atrium-left superior PV junction. 4D flow MRI can clarify the altered hemodynamics underlying thrombus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…There is only one case report that evaluated the blood flow in the LA after LUL. 10 Phase-contrast MRI-based evaluation for the blood flow in the LA was first reported two decades ago. 11,12 Thanks to the improvement of the scan scheme and post-processing software for time-resolved 3D phase-contrast (4D flow), the detailed blood flow in the LA has been actively investigated by using this modality in the latter half of the decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one case report that evaluated the blood flow in the LA after LUL. 10 Phase-contrast MRI-based evaluation for the blood flow in the LA was first reported two decades ago. 11,12 Thanks to the improvement of the scan scheme and post-processing software for time-resolved 3D phase-contrast (4D flow), the detailed blood flow in the LA has been actively investigated by using this modality in the latter half of the decade.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,16 In the same context, one previous case report utilizing 4D flow MRI suggested that abnormal LA blood flow after LUL causes PV stump thrombosis, resulting in embolic cerebral infarction. 10 The purpose of the current study was to clarify the blood flow pattern in the LA potentially causing the formation of thrombosis after LUL. The blood flow in the LAwas evaluated and compared between LUL patients with and without thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…To accurately capture both the high-and low-velocity blood flow, multivelocity encoding (multi-VENC) 4D flow MRI with a wide dynamic range of target blood flow velocity has been proposed. 63,[65][66][67][68]…”
Section: Aortic Dissectionmentioning
confidence: 99%
“…One of the hypotheses to explain the higher risk of thrombosis in this specific group is the existence of a longer pulmonary vein (PV) stump after LUL, which causes blood flow stasis resulting in the formation of the embolic source. 46,47,55 In addition to altered flow in the vein stump, the postoperative blood flow changes in the LA are supposed to further promote the formation of thrombosis [56][57][58][59] (Fig. 7).…”
Section: D Flow Mri Assessment Of Post-lung Surgerymentioning
confidence: 99%